NORMATIVE REVIEW OF LEGAL PROTECTION FOR MINORITY SHAREHOLDERS IN LIMITED LIABILITY COMPANIES IN INDONESIA (NORMATIVE LEGAL ANALYSIS) - Nasution , Emmi Rahmiwita; Saleha , Dwi; Inayah, Iin (Gapenas Publisher, 2025)
This study provides a normative legal analysis of the protection of minority shareholders in limited liability companies (Perseroan Terbatas/PT) in Indonesia. Minority shareholders often face unequal treatment due to the dominance of majority shareholders in decision-making, leading to potential abuse and neglect of their rights. Using a doctrinal approach, the research examines the legal framework under Law No. 40 of 2007 on Limited Liability Companies and related regulations, focusing on mechanisms such as derivative suits, company dissolution rights, accountability of directors and commissioners, and access to information. The analysis reveals that while Indonesia’s legal system formally recognizes these protections, their practical enforcement is hindered by high ownership thresholds, judicial inconsistency, lengthy litigation processes, and limited shareholder awareness. Comparative perspectives from jurisdictions such as the United States, United Kingdom, Singapore, and Malaysia highlight Indonesia’s need to strengthen its enforcement mechanisms and corporate governance practices. The study concludes that lowering procedural barriers, enhancing judicial consistency, promoting alternative dispute resolution, and improving legal literacy are crucial to ensuring effective protection of minority shareholders. Strengthening these protections not only guarantees fairness for shareholders but also contributes to investor confidence and sustainable corporate development in Indonesia.